2020
DOI: 10.1213/ane.0000000000004424
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Postpartum Hemorrhage in the United States From 2010 to 2014

Abstract: Postpartum hemorrhage (PPH) is a leading cause of morbidity and mortality in the United States; its prevalence increased during the 1990s–2000s. The purpose of this study was to reevaluate trends in PPH using the National Inpatient Sample. From 2010 to 2014, the prevalence of PPH increased from 2.9% (95% confidence interval [CI], 2.7%–3.1%) to 3.2% (95% CI, 3.1%–3.3%) of deliveries. Adjusting for PPH risk factors did not substantially attenuate this trend. Among patients with PPH, there was a decline in associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 17 publications
5
45
0
2
Order By: Relevance
“…Among the five studies on LENI conducted worldwide since 2002, researchers reported various incidence rates: 0.3% (Tournier et al, 2019), 0.6% (Dar et al, 2002), 0.92% (Wong et al, 2003), 0.96% (Haller et al, 2017), and 2.3% (Richard et al, 2017). These reported rates are similar to those for shoulder dystocia (0.2%-3%; American College of Obstetricians and Gynecologists Committee on Practice Bulletins-Obstetrics, 2017), postpartum venous thrombosis (0.05%-0.2%; American College of Obstetricians and Gynecologists Committee on Practice Bulletins-Obstetrics, 2018), and postpartum hemorrhage (3%; Reale et al, 2020). Notably, while these three complications are well-known and have associated evidence-based practice and training guidelines, LENI remains unfamiliar to many health care providers.…”
Section: Introductionsupporting
confidence: 69%
“…Among the five studies on LENI conducted worldwide since 2002, researchers reported various incidence rates: 0.3% (Tournier et al, 2019), 0.6% (Dar et al, 2002), 0.92% (Wong et al, 2003), 0.96% (Haller et al, 2017), and 2.3% (Richard et al, 2017). These reported rates are similar to those for shoulder dystocia (0.2%-3%; American College of Obstetricians and Gynecologists Committee on Practice Bulletins-Obstetrics, 2017), postpartum venous thrombosis (0.05%-0.2%; American College of Obstetricians and Gynecologists Committee on Practice Bulletins-Obstetrics, 2018), and postpartum hemorrhage (3%; Reale et al, 2020). Notably, while these three complications are well-known and have associated evidence-based practice and training guidelines, LENI remains unfamiliar to many health care providers.…”
Section: Introductionsupporting
confidence: 69%
“…In Canada, from 2001 to 2009, the incidence of PPH increased from 6.0 to 7.9% and from 1.4 to 2.7%, in vaginal deliveries and cesarean section cases, respectively (4). A nationwide study from the US also revealed that the incidence of PPH increased from 2.9 to 3.2% from 2010 to 2014 (9).Research from other countries also revealed similar results (5).…”
Section: Introductionmentioning
confidence: 81%
“…A study including 8.5 million pregnant women in the US revealed that the incidence of PPH was 2.8% in 2008 (7). In 2014, another larger study including >30 million patients reported a similar rate of 3.2% (9). In Canada, research in 2009 reported a 7.9% incidence of PPH in vaginal deliveries and 2.7% in cesarean section cases (4).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the incidence of PPH appears to be increasing. [5][6][7] Women with postpartum uterine atony have an increased risk of obstetric morbidity. The risk of morbidity in women who experience uterine atony after cesarean delivery was increased among African American and Hispanic compared with White women, in women with multiple gestation, placenta previa, ASA Physical Status 3 or 4, exposure to general anesthesia, and multiple prior cesarean deliveries.…”
mentioning
confidence: 99%